Pengaruh Pengalaman Belajar Mata Pelajaran Produk Kreatif Kewirausahaan, Lingkungan Keluarga dan Efikasi Diri terhadap Minat Bisnis Start-Up Siswa Kelas XI SMKS X (Lembaga Pengembangan Kinerja Dosen, 2026)
The high unemployment rate of Vocational High School (SMK) graduates demands the strengthening of entrepreneurship education to encourage the younger generation to be more independent in their careers. This study aims to analyze the influence of learning experience in Creative Products and Entrepreneurship subjects, family environment, and self-efficacy on interest in starting a start-up business in grade XI students of SMK X. The research method uses a quantitative approach with survey techniques. The research sample amounted to 206 students who were selected purposively. The data collection instrument was in the form of a questionnaire which was then analyzed using multiple linear regression. The results showed that learning experience (X1) did not have a significant effect on the interest in starting a start-up business. However, the family environment (X2) and self-efficacy (X3) were shown to have a positive and significant influence on these interests. Simultaneous analysis of the three independent variables indicated that together learning experience, family environment, and self-efficacy had a significant effect on students' entrepreneurial interest. These findings confirm that external factors, especially family support, and internal factors in the form of self-efficacy are more dominant in influencing entrepreneurial interest than learning experiences at school. The implication of this research is the need for entrepreneurial learning strategies that are more applicable, innovative, and able to relate the material to real practices in daily life. In addition, family involvement is an important aspect in fostering students' confidence and motivation to start a business. Thus, strengthening the synergy between entrepreneurship education in schools and the role of the family will be a strategic step in forming a generation of young entrepreneurs who are independent, competitive, creative, innovative, and adaptive to the development of digital technology, while being able to create new sustainable job opportunities in society.